In-silico Mining and Characterization of Drought Tolerance Genes in Wheat (Triticum aestivum L.) using a Digital Candidate Gene Approach - Kumar, Pradeep; Hathiaram, Dharavath; Malik, Aayushi; Adhana, Preeti; Sharma, Pradeep Kumar (International Journal of Bio-resource and Stress Management, 2026)
The study was conducted in 2019 at the Department of Genetics and Plant Breeding, Chaudhary Charan Singh University, Meerut, Uttar Pradesh, India. The research aimed to identify drought-responsive candidate genes in wheat (Triticum aestivum L.) through a comparative genomics approach using previously characterized drought-related genes from barley and rice. A total of 21 reported genes from these reference crops were examined to identify their putative wheat orthologues based on sequence homology and genome annotation using publicly available wheat genomic resources. RNA-seq datasets retrieved from the WheatExp database were analysed to assess tissue-specific expression patterns of the identified wheat orthologues under drought conditions. Functional domain analysis was further performed to predict the biological roles of the encoded proteins in drought tolerance mechanisms. Six wheat orthologues were identified, encoding proteins such as alcohol dehydrogenase, chaperonin, dehydrin, and serine/threonine protein kinase. These genes exhibited distinct and reproducible expression profiles across tissues including leaves, roots, grains, spikes, and stems under drought stress. Functional annotation revealed their involvement in osmotic adjustment, protein stabilization, cellular protection, and signal transduction during water-deficit conditions. The identified drought-responsive wheat genes represent potential targets for downstream functional validation and molecular breeding. The findings provide gene-level insights into drought-related mechanisms in wheat and offer a genomic resource for developing improved genotypes suited to water-limited environments.